Helicons and magnetoimpurity waves in layered conductors - Gvozdikov, V.M.; Ermolaev, A.M.; Vega-Monroy, R. (Физика низких температур, 1999)
It is shown that local electron states, caused by impurities in a layered conductor placed in an external magnetic field, give rise to resonant corrections Δσαβ(ω) to the high-frequency conductivity tensor Δσαβ(ω) of the layers. These corrections appear due to the resonant transitions of electrons between the Landau levels and the local states and change dramatically the spectrum of collective electromagnetic oscillations in the system because of the "branch crossing" nearby the frequency ω₀(ħω₀ is the local state energy). As a result, a new magnetoimpurity wave, ω₋k, appears in the spectrum in addition to the helicon mode,ω₊k, which is known to exist in a pure layered conductor in a perpendicular magnetic field (k is the wave vector along the magnetic field). In the long wavelength limit, kα<<1 the helicon-like mode w₊k has a gap of the order of w₀ , whereas the magnetoimpurity mode in this limit goes to zero w₋k~(kα)² (a is the distance between adjacent layers). The small damping of these modes due to the broadening of the Landau levels and the magnetoimpurity levels are also calculated.